The walls have eyes - Praveen Ramesh (Nanyang Technological University, 2022)
What was once already a demographic forced into discretion and ‘hiding’ through ways such as heterosexual marriage for the sake of normalcy, are even less visible in contemporary times and are further sidelined not just by discrimination but urbanization. We know due to the peak in LGBTQ Culture in this area 30 years ago that we have a high population of LGBTQ elderly and aging population in the present, yet we do not visibly come across any public space where we see them in their own skin. The tri intersection of historically rich infrastructure such as Shophouses in the Chinatown district, the existence of High Density of Cultural/Religious Sites, and the history of the LGBTQ Community, form the mostly unlikely yet potent, untapped synergy that then offers us a possibility for reconciliation to take place through the explorative approach of speculative design.